NEW PROBIOTIC AGENT FOR THE BOWEL MICROFLORA CORRECTION IN INFANTS - E. S. Keshishyan ("Paediatrician" Publishers LLC, 2013)
Characteristics of a new probiotic - a biological additive, developed specially for children - and indications for its usage are shown in this article.